Clinical, Diagnostic, and Therapeutic Aspects of Growth Hormone Deficiency During the Transition Period: Review of the Literature - Spaziani, Matteo; Tarantino, Chiara; Tahani, Natascia; Gianfrilli, Daniele; Sbardella, Emilia; Isidori, Andrea M.; Lenzi, Andrea; Radicioni, Antonio F. (Frontiers in Endocrinology, 2021)
The role of growth hormone (GH) during childhood and adulthood is well established. Once final stature is reached, GH continues to act during the transition, the period between adolescence and adulthood in which most somatic and psychological development is obtained. The achievement of peak bone mass represents the most relevant aspect of GH action during the transition period; however, equally clear is its influence on body composition and metabolic profile and, probably, in the achievement of a complete gonadal and sexual maturation. Despite this, there are still some aspects that often make clinical practice difficult and uncertain, in particular in evaluating a possible persistence of GH deficiency once final stature has been reached. It is also essential to identify which subjects should undergo re-testing and, possibly, replacement therapy, and the definition of unambiguous criteria for therapeutic success. Moreover, even during the transition phase, the relationship between GH substitution therapy and cancer survival is of considerable interest. In view of the above, the aim of this paper is to clarify these relevant issues through a detailed analysis of the literature, with particular attention to the clinical, diagnostic and therapeutic aspects.